Determination of prescribed and designer benzodiazepines and metabolites in influent wastewater. Issue 28 (6th July 2020) - Bade, Richard; Ghetia, Maulik; White, Jason M.; Gerber, Cobus
Abstract : With illicit and designer benzodiazepines becoming more prevalent in the community, this work presents the validation and application of an analytical method for prescribed benzodiazepines and metabolites in wastewater. Abstract : Benzodiazepines are important prescription pharmaceuticals used to help in the treatment of anxiety and sleep disorders. However, they also have a strong potential for abuse. In this respect, illicit benzodiazepines, i.e. not prescribed in Australia and designer benzodiazepines, which are new compounds that are not legally prescribed in any jurisdiction, have emerged in the illicit Australian market in recent years. Designer benzodiazepines are a new class of new psychoactive substances (NPS) and are particularly dangerous due to limited toxicity information and propensity to be mistaken for conventional benzodiazepines, leading to severe side effects and potentially death. It is therefore important to assess the prevalence of the use of these compounds in the community. The current work presents a validated liquid chromatography-mass spectrometry method for 20 prescribed and designer benzodiazepines and metabolites: 7-amino nimetazepam, alpha-hydroxy alprazolam, alprazolam, clonazepam, delorazepam, deschloroetizolam, diazepam, diclazepam, etizolam, flubromazepam, flunitrazepam, lorazepam, lormetazepam, meclonazepam, midazolam, nimetazepam, nitrazepam, oxazepam, pyrazolam and temazepam. Quetiapine, a prescription sedative drug that has been diverted for non-medical use, was also validated. Limits of quantification were predominantly below 10 ng L −1, except for the ubiquitous oxazepam, quetiapine and temazepam, which were between 75–300 ng L −1 . Stability, recovery and matrix effects were also examined. Finally, this method was applied to influent wastewater from South Australia, which showed the presence of many benzodiazepines including the NPS etizolam.